PERAN LIFE CYCLE STAGE DALAM MEMODERASI HUBUNGAN ANTARA INTELLECTUAL CAPITAL DISCLOSURE DAN NILAI PERUSAHAAN - Arif Pujianto (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2016)
The purpose of this study to determine the life cycle stage moderate the relationship of intellectual capital disclosure and corporate value. Components of intellectual capital disclosure  is human capital disclosure, structure capital disclosure and customer capital disclosure. Life cycle stage of research needs to be reviewed as there are differences of opinion on previous research. Samples used were drawn taken from manufacturing companies listed on the Stock Exchange during the period 2009 - 2011 as many as 70 companies. The method used in this study using multiple regression method. The results of this study demonstrate the value of intellectual capital disclosure and the company does not have a significant effect. Life cycle stages in moderating the relationship of intellectual capital disclosure and corporate value had no significant effect. Results of this study can provide useful information for the company in making policy, particularly the role of the company in developing the Indonesian economy. This research has an important role in the management accounting literature on disclosure of intellectual capital in particular